SnO2 modified WO3 nanosheet composite gas-sensitive material as well as preparation method and application thereof

By growing WO3 nanosheets in situ on ceramic tubes and modifying SnO2 particles, SnO2 modified WO3 nanosheet composite gas-sensitive material was prepared, which solved the problems of high working temperature and poor selectivity of existing WO3 materials, and achieved efficient detection of nitrogen dioxide.

CN119660804APending Publication Date: 2025-03-21UNIV OF JINAN
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411732914.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

As a gas-sensitive material, the existing WO3 has problems such as high operating temperature, poor gas selectivity, long response and recovery time, especially in the detection of nitrogen dioxide.

Method used

By growing WO3 nanosheets in situ on a ceramic tube and modifying SnO2 particles thereon by secondary hydrothermal method, the composite gas-sensitive material of SnO2 modified WO3 nanosheets was prepared.

Benefits of technology

It achieves extremely high response and selectivity to nitrogen dioxide at low temperatures, significantly reduces the operating temperature and improves the gas-sensitive properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660804A_ABST
    Figure CN119660804A_ABST
Patent Text Reader

Abstract

The invention discloses a SnO2 modified WO3 nanosheet composite gas-sensitive material as well as a preparation method and application thereof, and belongs to the technical field of inorganic composite materials. The preparation method comprises the following steps: dissolving WCl6 in ethanol, adding into a reaction kettle provided with a ceramic tube, carrying out hydrothermal reaction at 170-190 DEG C for 5-8 hours, taking out the ceramic tube, drying, and annealing to obtain a ceramic tube loaded with WO3 nanosheets; the preparation method comprises the following steps: dissolving SnO2, tin chloride and urea in water to obtain a mixed solution, adding the mixed solution into a reaction kettle filled with a ceramic tube loaded with a WO3 nanosheet, carrying out a hydrothermal reaction at 90-100 DEG C for 1-4 hours, taking out the ceramic tube after the reaction is finished, and drying to obtain the SnO2 modified WO3 nanosheet composite gas sensitive material, and enabling the SnO2 modified WO3 nanosheet to grow on the ceramic tube in situ. The preparation method is simple, the product is high in crystallinity and good in stability and is suitable for preparing a gas sensitive sensor material with high economical efficiency, and a sensor prepared from the SnO2 modified WO3 nanosheet composite gas sensitive material can effectively improve the gas sensitive performance of WO3 and shows an extremely high response value to nitrogen dioxide at a low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation and application of inorganic composite materials, and specifically relates to a SnO2 modified WO3 nanosheet composite gas-sensitive material and a preparation method and application thereof. Background Art

[0002] With the improvement of modern industrial level, industrial production has created huge economic value while also causing harm to the environment. Nitrogen oxides, as an important component of air pollutants, are mainly produced by automobile exhaust and industrial emissions. Among them, the representative gas nitrogen dioxide is highly toxic and irritating, which has great harm to the ecological environment and human health. Therefore, the nitrogen dioxide content is an important indicator in air quality detection. To implement these prevention and control measures, we must first achieve efficient detection of harmful gases. Therefore, gas sensors stand out in gas monitoring with their advantages such as sensitivity and convenience.

[0003] Gas sensors are devices that detect gas based on gas-sensitive properties, and there are many types of them. Among them, semiconductor gas sensors are widely used due to their practicality and a wide variety of sensitive materials. According to the working principle, semiconductor gas sensors can be divided into two types: resistive and non-resistive. Resistive sensors are highly praised for their simple working principle, low cost and excellent stability. WO3, as an n-type semiconductor, has the advantages of wide band gap, high thermal stability and easy synthesis, and is widely used in the field of gas sensors. However, there are also some defects, such as high operating temperature, poor gas selectivity, and long response and recovery time.

[0004] With the continuous development of gas sensing technology, due to the limitations of the physical and chemical properties of single metal oxides, its gas sensing performance is difficult to further improve. Compared with single metal oxides, composite metal oxides have flexible chemical components, and the heterojunctions formed between different components have special synergistic effects and have more research potential. Based on the construction of heterostructures, changes in the band structure of materials can be triggered, while providing more active sites, thereby significantly improving the catalytic activity of materials. This change has a positive effect on enhancing the gas-sensing properties of sensitive materials. WO3 and SnO2 are two important n-type semiconductor materials, which are widely used in the field of gas sensors.

[0005] Patent CN 116448819 A discloses a method for detecting trimethylamine gas using SnO2-WO3 gas-sensitive material. The SnO2-WO3 gas-sensitive material is prepared by a two-step hydrothermal method: tungstic acid (H2WO4) is dispersed in 50 mL of H2O and 34 mL of H2O2, and the obtained mixed solution is heated to 95°C in a water bath, and then the solution is stirred until it is clear; water is added to dilute it to 200 mL to obtain a tungstic acid (H2WO4) solution; acetonitrile and HCl solution are added to the tungstic acid solution, and oxalic acid and urea are added until it is stirred and clarified; the solution is transferred into a closed reactor with a capacity of 50 mL, heated to 180°C in an oven for 12 hours, and the powder is collected after natural cooling, washed, and dried to obtain pure WO3 powder; stannous chloride dihydrate (SnCl2·2H2O) and thiourea (CH4N2S) are dissolved in deionized water and stirred at room temperature for 30 minutes; WO3 powder is ultrasonically dispersed and added to the above solution, stirred at room temperature for 6 hours, centrifuged, washed, dried, After calcination at 300°C for 2h, the SnO2‑WO3 gas-sensitive material was obtained, which showed high sensitivity, good selectivity and fast response‑recovery characteristics to trimethylamine.

[0006] However, there is no report on the specific detection of nitrogen dioxide by SnO2‑WO3 materials in the prior art. Summary of the invention

[0007] In view of the above problems, the present invention provides a SnO2 modified WO3 nanosheet composite gas-sensitive material and its preparation method and application. The SnO2 modified WO3 nanosheets are in-situ grown on a ceramic tube, which solves the problems of high working temperature, poor gas selectivity, and long response and recovery time of WO3 as a gas-sensitive material in the prior art, and can be applied to the detection of nitrogen dioxide.

[0008] The present invention is achieved through the following technical solutions: A method for preparing a SnO2-modified WO3 nanosheet composite gas-sensitive material comprises the following steps: (1) Preparation of ceramic tubes loaded with WO3 nanosheets: WCl6 was dissolved in ethanol and added to a reactor containing a ceramic tube. The reaction was carried out at 170-190°C for 5-8 hours. The ceramic tube was taken out and dried and annealed to obtain a ceramic tube loaded with WO3 nanosheets. (2) Preparation of SnO2-modified WO3 composite gas-sensitive material: Tin chloride and urea are dissolved in water to obtain a mixed solution, which is added to a reactor containing a ceramic tube loaded with WO3 nanosheets in step (1), and subjected to hydrothermal reaction at 90-100 °C for 1-4 h. After the reaction is completed, the ceramic tube is taken out and dried to obtain a SnO2-modified WO3 nanosheet composite gas-sensitive material.

[0009] Furthermore, the annealing treatment condition in step (1) is 450-550° C. for 1-3 hours.

[0010] Furthermore, the heating rate during the annealing treatment in step (1) is 1-3 °C / min.

[0011] Furthermore, in step (1), the concentration of WCl6 is 0.01-0.02 g / mL; in step (2), the tin chloride is SnCl2·2H2O, the concentration of SnCl2·2H2O in the mixed solution is 0.01-0.03 g / mL, and the concentration of urea is 0.002-0.006 g / mL.

[0012] Furthermore, the ceramic tube in step (1) is an alumina ceramic tube, and the ceramic tube is ultrasonicated with deionized water and ethanol for 5 minutes respectively before use.

[0013] Furthermore, in step (1), the hydrothermal reaction is carried out at 180°C for 6 hours. The WO3 nanosheets grown at this temperature and reaction time are large in size, evenly distributed, densely grown, and have good crystallinity.

[0014] Furthermore, the hydrothermal reaction in step (2) is carried out at 90-100° C. for 1.5-2 h.

[0015] Furthermore, in step (2), the hydrothermal reaction is carried out at 95°C for 2h. The SnO2-modified WO3 composite material grown at this temperature and reaction time has SnO2 in the form of nanoparticles uniformly distributed on the WO3 nanosheets, and the size and number of SnO2 particles increase with the increase of hydrothermal time.

[0016] In the present invention, the SnO2 modified WO3 nanosheet composite gas-sensitive material is prepared by the preparation method.

[0017] In the present invention, the SnO2 modified WO3 nanosheet composite gas-sensitive material is used in detecting nitrogen dioxide.

[0018] Beneficial Effects (1) The present invention grows WO3 nanosheets upright on the surface of an alumina ceramic tube, and then calcines them in a tube furnace to prepare a pure phase WO3 material. The preparation method is simple and can obtain a nanosheet structure with uniform morphology and size; (2) The present invention adopts a secondary hydrothermal method to modify SnO2 particles on WO3 nanosheets, grows them in situ on a ceramic tube, and prepares SnO2-modified WO3 composite gas-sensitive materials. The prepared WO3 and SnO2 are evenly distributed on the ceramic tube, which is conducive to giving full play to the advantages of nn heterojunction band bending, electron transfer, multiple active sites, increased surface area, etc., and has a lower operating temperature; (3) The preparation method of the present invention is simple, the product has high crystallinity and good stability, and is suitable for preparing highly economical gas sensor materials. In addition, the sensor prepared by SnO2-modified WO3 nanosheet composite gas-sensitive material can effectively improve the gas-sensitive performance of WO3 and show an extremely high response value to nitrogen dioxide at low temperature. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a scanning electron microscope (SEM) image of the ceramic tube loaded with WO3 nanosheets prepared in Example 1; Figure 2 is the X-ray diffraction (XRD) pattern of the ceramic tube loaded with WO3 nanosheets prepared in Example 1; Figure 3 This is a scanning electron microscope (SEM) image of the SnO2-modified WO3 nanosheet composite gas-sensitive material prepared in Example 1; Figure 4 The scanning electron microscope (SEM) images of SnO2-modified WO3 nanosheet composite gas-sensitive materials prepared under different conditions in Examples 1 to 4; Figure 5 It is the response value curve of different gas-sensitive materials at different temperatures; Figure 6 This is a diagram showing the selectivity of different gas-sensitive materials for different gases; Figure 7 This is the response curve of different gas-sensitive materials to different concentrations of nitrogen dioxide. DETAILED DESCRIPTION

[0020] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples, and all technologies implemented based on the above contents of the present invention belong to the scope of the present invention.

[0021] Example 1 (1) The alumina ceramic tube was placed in deionized water and ethanol and cleaned with an ultrasonic instrument for 5 minutes, then dried for later use; (2) Place the cleaned alumina ceramic tube into the inner lining of a polytetrafluoroethylene reactor, slowly drip WCl6 ethanol solution (add 23 ml of anhydrous ethanol to 0.4 g of WCl6 and stir on a magnetic stirrer for 15 min), seal it, place it in a forced air drying oven for hydrothermal reaction at 180 °C for 6 h, take out the ceramic tube, clean and dry it, place it in a tubular furnace and heat it at 500 °C for 2 h at a heating rate of 2 °C / min to obtain a ceramic tube loaded with WO3 nanosheets. The scanning electron microscopy results are shown in Figure 2. Figure 1 As shown, from Figure 1 It can be seen that WO3 is a nanosheet structure grown in situ on the ceramic tube, and the WO3 nanosheets grow densely and uniformly; the XRD spectrum of the ceramic tube loaded with WO3 nanosheets is shown in Figure 2 As shown, from Figure 2 It can be seen that the WO3 nanosheets have good crystallinity and no other impurity peaks appear; (3) The ceramic tube loaded with WO3 nanosheets in step (1) is placed in the inner lining of a reactor, and a mixed solution of SnCl2·2H2O and urea is added (0.4605 g SnCl2·2H2O and 0.1213 g urea are added with 20 ml deionized water respectively, stirred for 20 min, and then mixed and stirred for 20 min. After sealing, the tube is placed in a forced air drying oven for hydrothermal treatment at 95 °C for 2 h. After the hydrothermal treatment is completed, the ceramic tube is taken out from the cooled reactor, cleaned, and placed in a drying oven for constant temperature drying at 60 °C for 1 h to obtain a SnO2-modified WO3 nanosheet composite gas-sensitive material. The SnO2-modified WO3 nanosheet structure is in situ grown on the ceramic tube. The scanning electron microscope image of the SnO2-modified WO3 nanosheet composite gas-sensitive material is shown in FIG. Figure 3 As shown, from Figure 3 It can be seen that uniform SnO2 nanoparticles grow on the surface of the ceramic tube loaded with WO3.

[0022] Embodiment 2-4 The reaction time in step (3) of Example 1 was changed, and the remaining steps were the same as Example 1, as shown in Table 1 below.

[0023] Table 1 The scanning electron microscope (SEM) image of the SnO2 modified WO3 nanosheet composite gas-sensitive material prepared in Example 2 is as follows: Figure 4 As shown in (a), it can be clearly seen that the surface SnO2 nanoparticles are dispersed on the WO3 sheet and are small in size; the scanning electron microscope (SEM) image of the SnO2 modified WO3 nanosheet composite gas-sensitive material prepared in Example 1 is as follows Figure 4 As shown in (b), the SnO2-modified WO3 composite material grown at this temperature and reaction time has SnO2 nanoparticles uniformly distributed on the WO3 nanosheets with moderate sizes; the scanning electron microscopy (SEM) results of the SnO2-modified WO3 nanosheet composite gas-sensitive material prepared by the method of Example 3 are shown in Figure 4 As shown in (c), it can be found that the number of SnO2 particles on the surface increases and the size becomes larger; the scanning electron microscopy (SEM) results of the SnO2 modified WO3 nanosheet composite gas sensing material prepared by the method of Example 4 are as follows Figure 4 As shown in (d), SnO2 is widely distributed on the surface of WO3 nanosheets, SnO2 particles aggregate, and the thickness of the nanosheets increases.

[0024] Application test of gas sensitive materials The ceramic tube (WO3) loaded with WO3 nanosheets prepared in step (2) of Example 1, the SnO2-modified WO3 nanosheet composite gas-sensitive material (WO3- SnO2 (2 h)) prepared in step (3) of Example 1, the SnO2-modified WO3 nanosheet composite gas-sensitive material (WO3- SnO2 (1 h)) prepared in Example 2, the SnO2-modified WO3 nanosheet composite gas-sensitive material (WO3-SnO2 (3 h)) prepared in Example 3, and the SnO2-modified WO3 nanosheet composite gas-sensitive material (WO3- SnO2 (4 h)) prepared in Example 4 were welded to the base to prepare the corresponding gas sensors, and the working temperature, response value and selectivity of different materials were detected and analyzed. 1) Test the response values ​​of four gas-sensitive materials (WO3, WO3- SnO2 (1 h), WO3- SnO2 (2 h), WO3- SnO2 (3 h), WO3-SnO2 (4 h)) to nitrogen dioxide at different temperatures. The concentration of nitrogen oxide gas used in the test is 50 ppm. The test results are as follows: Figure 5 It was found that SnO2 modified WO3 composite gas-sensitive material (WO3- SnO2 (2 h)) had the best gas-sensitive performance at 100 °C, and was significantly stronger than the other three gas-sensitive materials, and the operating temperature was greatly reduced.

[0025] 2) Test the response values ​​of five gas-sensitive materials (WO3, WO3- SnO2 (1 h), WO3- SnO2 (2 h), WO3- SnO2 (3 h), WO3-SnO2 (4 h)) in different gas atmospheres (acetone, formaldehyde, triethylamine, nitrogen dioxide, ethanol, isopropanol, ammonia, trimethylamine). The gas concentration is 50 ppm and the temperature is 100 °C. The test results are as follows: Figure 6 As shown, it was found that the SnO2 modified WO3 nanosheet composite gas-sensitive material (WO3-SnO2 (2 h)) prepared in Example 1 had extremely high selectivity for nitrogen dioxide.

[0026] 3) Test the response values ​​of five gas-sensitive materials (WO3, WO3- SnO2 (1 h), WO3- SnO2 (2 h), WO3- SnO2 (3 h), WO3- SnO2 (4 h)) to different concentrations of nitrogen dioxide. Set the detection temperature to 100 °C. The test results are as follows: Figure 7 As shown in the figure, it was found that with the increase of nitrogen dioxide concentration, the gas response value of SnO2 modified WO3 composite gas sensitive material (WO3-SnO2 (2 h)) continued to increase, and it still had a high gas response value at low concentration.

Claims

1. A method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material, characterized in that: The following steps are involved: (1) Preparation of ceramic tubes loaded with WO3 nanosheets: WCl6 was dissolved in ethanol and added to a reactor containing a ceramic tube. The reaction was carried out at 170-190°C for 5-8 hours. The ceramic tube was taken out and dried and annealed to obtain a ceramic tube loaded with WO3 nanosheets. (2) Preparation of SnO2-modified WO3 composite gas-sensitive material: Tin chloride and urea are dissolved in water to obtain a mixed solution, which is added to a reactor containing a ceramic tube loaded with WO3 nanosheets in step (1), and subjected to hydrothermal reaction at 90-100 °C for 1-4 h. After the reaction is completed, the ceramic tube is taken out and dried to obtain a SnO2-modified WO3 nanosheet composite gas-sensitive material.

2. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: The annealing treatment conditions in step (1) are 450-550°C for 1-3 hours.

3. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 2, characterized in that: The heating rate during the annealing treatment in step (1) is 1-3 °C / min.

4. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: The concentration of WCl6 in step (1) is 0.01-0.02 g / mL; the tin chloride in step (2) is SnCl2·2H2O, the concentration of SnCl2·2H2O in the mixed solution is 0.01-0.03 g / mL, and the concentration of urea is 0.002-0.006 g / mL.

5. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: The ceramic tube in step (1) is an alumina ceramic tube, and the ceramic tube is ultrasonicated with deionized water and ethanol for 5 minutes respectively before use.

6. The method for preparing the SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: In step (1), the hydrothermal reaction was carried out at 180°C for 6 hours.

7. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: In step (2), the hydrothermal reaction is carried out at 90-100°C for 1.5-2h.

8. The method for preparing SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 1, characterized in that: In step (2), the hydrothermal reaction was carried out at 95 °C for 2 h.

9. A SnO2 modified WO3 nanosheet composite gas-sensitive material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the SnO2 modified WO3 nanosheet composite gas-sensitive material according to claim 9 in detecting nitrogen dioxide.

Citation Information

Cited By

  • A sulfur dioxide gas sensor and a method for manufacturing the same

    CN122545609A

  • A sulfur dioxide gas sensor and a method for manufacturing the same

    CN122545609B